Polyphyllin I Induces Cell Cycle Arrest and Cell Apoptosis in Human Retinoblastoma Y-79 Cells through Targeting p53 - Zhu, Xue; Wang, Ke; Zhang, Kai; Pan, Yi; Zhou, Fanfan; Zhu, Ling (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Retinoblastoma is the most common intraocular malignant tumor in childhood. Although external beam radiation and enucleation are effective to control retinoblastoma, eye salvage and vision preservation are still significant challenges. Polyphyllin I (PPI), a natural compound extracted from Paris polyphylla rhizomes, has a wide range of activities against many types of cancers. However, the potential effect of this herbal compound on retinoblastoma has not yet been investigated. Method: In the present study, we evaluated the cytotoxic effect of PPI on human retinoblastoma Y-79 cells as well as its underlying molecular mechanism. Our results indicated that PPI treatment significantly inhibited cell proliferation, arrested the cell cycle at G2/M phase and induced cell apoptosis of Y79 cells through the mitochondrial- dependent intrinsic pathway. Moreover, p53 is involved in PPI-induced cytotoxicity in human retinoblastoma Y-79 cells. Exposure to 10 μM PPI for 48 h dramatically induced the expression levels of p53, phosphorylated- p53 and acetylated-p53. Furthermore, blockade of p53 expression effectively attenuated PPI-induced cell cycle arrest and cell apoptosis in Y-79 cells. Result: These results demonstrated that PPI exhibits anti-proliferation effect on human retinoblastoma Y-79 cells through modulating p53 expression, stabilization and activation. This information shed light on the potential application of PPI in retinoblastoma therapy.
Keywords: paris polyphylla rhizomes